Gadget addiction among university students: a study in UiTM Kedah / Nurul Anisha Ab Halim and Nur Atiyah Mohd Yusof - Ab Halim, Nurul Anisha; Mohd Yusof, Nur Atiyah (2019)
This study was conducted to determine the factors that influence gadget addiction among university students in UiTM Kedah. This study focused on the discussion of the findings based on quantitative study. Data of this study were collected by a set of questionnaire containing five section which is demographic data of respondents, gadget addiction, social interaction, lifestyle and times spent. The sampling technique that have been used was simple random sampling. Data were analysed by using Statistical Package for the Social Science (SPSS) version 24. The result shows that lifestyle is the most influential factor of gadget addiction among university students in UiTM Kedah. The significance of this study is to contribute to the body of knowledge in gadget addiction, to assist the researcher in understanding gadget addiction towards university students and to create awareness regarding gadget addiction. The recommendation has been provided in this study in order to prevent the students from becoming high extent of gadget addiction and also to cater the limitations. The discussion and conclusion were elaborated in this study.